2003
DOI: 10.1074/jbc.m308152200
|View full text |Cite
|
Sign up to set email alerts
|

The Co-repressor Hairless Protects RORα Orphan Nuclear Receptor from Proteasome-mediated Degradation

Abstract: ROR␣ is a constitutively active orphan nuclear receptor essential for cerebellar development and is previously shown to regulate genes involved in both myogenesis and adipogenesis. The transcriptional activity of ROR␣ is dependent on the presence of a ubiquitous ligand and can be abolished by interaction with Hairless (Hr), a ligand-oblivious nuclear receptor co-repressor. In this study, we first demonstrate that ROR␣ is a shortlived protein and that treatment with the MG-132 proteasome inhibitor results in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 57 publications
1
25
0
Order By: Relevance
“…Accumulated COX-1 protein was detected at 10 min after initiation of treatment with A23187 and MG132, and its level increased in a time-dependent manner (Figure 2A), suggesting that COX-1 is a likely substrate of the ubiquitin–proteasome complex, whereas COX-1 did not accumulate when cells were cultured in medium containing A23187 alone (Figure 2A); these results are consistent with previous results (Moraitis and Giguere, 2003; Mishra et al , 2009). To further investigate COX-1 degradation through the ubiquitin–proteasome system, we examined the time dependence of the effect of MG132 on the ubiquitination of the COX-1 protein in the cells.…”
Section: Resultssupporting
confidence: 91%
“…Accumulated COX-1 protein was detected at 10 min after initiation of treatment with A23187 and MG132, and its level increased in a time-dependent manner (Figure 2A), suggesting that COX-1 is a likely substrate of the ubiquitin–proteasome complex, whereas COX-1 did not accumulate when cells were cultured in medium containing A23187 alone (Figure 2A); these results are consistent with previous results (Moraitis and Giguere, 2003; Mishra et al , 2009). To further investigate COX-1 degradation through the ubiquitin–proteasome system, we examined the time dependence of the effect of MG132 on the ubiquitination of the COX-1 protein in the cells.…”
Section: Resultssupporting
confidence: 91%
“…The hairless gene product, HR, like the VDR, is involved in regulating hair growth. HR has recently been shown to function as a corepressor with VDR [24], thyroid hormone receptor (TR) [25], and the retinoic acid receptorrelated orphan receptor α (RORα) [26,27]. It has been suggested that VDR and HR regulate a common pathway(s) involved in the hair cycle and epithelial cell differentiation [24].…”
Section: Introductionmentioning
confidence: 99%
“…Mice lacking functional hairless (Hr) (Panteleyev et al, 1999; Sundberg et al, 1999) develop a hair follicle phenotype comparable to that seen in the VdrKO mouse. Hairless, which is a known corepressor to some nuclear receptors (Potter et al, 2001, 2002; Moraitis et al, 2002; Moraitis and Giguere, 2003), interacts directly with Vdr (Hsieh et al, 2003; Xie et al, 2006; Wang et al, 2007) and inhibits ligand dependent Vdr mediated transcription. Because of the parallel between VdrKO and hairless mice phenotypes, it has been hypothesized that Hr and Vdr converge to control hair cycling but the role of Hr in modulating ligand independent actions of Vdr as in hair follicle cycling is not known.…”
mentioning
confidence: 99%